The study on factors influence technophobia among part 5 of Diploma in Banking (DIB) students in UiTM Kedah / Sakinah Sariff - Sariff, sakinah (Faculty of Information Management, 2010)
Technophobia is the fear or dislike of advanced technology or complex devices especially computers. Technophobia generally arises when an individual is not able to adapt himself to the new technologies like computers. Therefore, a study of technophobia is conducted in order to examine the factors influence technophobia. This study also can make student realize about the existence of technophobia problem in themselves. This research seeks to determine the relations of independent variables and dependent variable. The dependent variable is technophobia. The independents variables are personal traits, exposure level and learning environment.